Sources of Missiological Knowledge - Skreslet, Stanley H. (International bulletin of mission research, 2025)
Missiology has become a complex, interdisciplinary, multicultural, and global research project. An attempt is made in the present essay to profile this wide-ranging scholarly community by describing three distinguishable constituent groups within the whole. The rather broad collection of methods now used to study mission is discussed, alongside the primary means scholars regularly utilize to share different kinds of missiological knowledge with each other apart from books. Reference is made to the current state of Jesuit studies and the recently published Oxford Handbook of Mission Studies, in order to illustrate the still-expanding reach of missiology.